BENEFITS OF SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) IN PREGNANCY, CHILDBIRTH, AND POSTPARTUM PERIOD : A LITERATURE REVIEW - Nasution, Nadhiati Awlia; Rachmawati, Anita; Nurihsan, Juntika; Susanti, Ari Indra; Sudirman, Siska Bradinda Putri (Universitas Aisyah Pringsewu, 2024)
Pregnancy, childbirth, and the postpartum period represent natural experiences for women, with physical and psychological changes occurring during these phases. During pregnancy, there are hormonal fluctuations that can affect the mother's mood and emotions. Therefore, psychological support is needed for pregnant women because it can prevent complications during labor and postpartum. To prevent these conditions, complementary therapies are needed, such as Spiritual Emotional Freedom Technique (SEFT) as a holistic midwifery care for the physical and emotional health of the mother. The focus of this study was to evaluate the benefits of SEFT therapy in the care of pregnant women during pregnancy, during labor, and postpartum period. The research methodology utilized a systematic literature review sourced from various databases including ProQuest, PubMed, Oxford, SCOPUS, ScienceDirect, SAGE Journal, and Google Scholar. The PRISMA protocol guided data extraction and categorization. Results Ten relevant articles identified that SEFT therapy contributes to improving maternal well-being and cardiovascular health during pregnancy. In addition, the therapy has been shown to reduce anxiety among pregnant, pre-cesarean section, and laboring mothers, and has demonstrated efficacy in reducing post-cesarean section pain and improving postpartum maternal sleep.